Experiment of Community Language Learning Method in Maharah Kalam Learning Foreign Language Development Institute (LPBA) at Al-Yasini Integrated Islamic Boarding School Pasuruan: Eksperimen Metode Community Language Learning dalam Pembelajaran Maharah Kalam Lembaga Pengembangan Bahasa Asing (LPBA) di Pondok Pesantren Terpadu Al-Yasini Pasuruan - Karimah, Ismaul; Hasyim, Mochamad; Taubah, Miftachul (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2024)
In learning Arabic, the learner must be involved in speaking practice. By developing speaking skills (maharah kalam), learner participants can interact with native Arabic speakers and Arabic society more effectively, but many learner participants are not confident in practicing Arabic in their environment. The Community Language Learning Method is a method in which the teacher, in this case, pays attention to the individual needs of the learner participants and what the learner's fears or problems are in Maharah Kalam learning. By arousing a feeling of being accepted by the environment (sense of community) in the learner participants, the teacher can mobilize the positive energy of the learner so that they are focused on Maharah Kalam learning. The purpose of this study was to find out the significance of the differences before and after the community language learning method experiment in Maharah Kalam learning. The results of this study were that according to SPSS 16 calculations in this study, the results of a significance value of less than 0.05, namely Sig.(0.000) < 0.05, so Ho was rejected, then Ha was accepted. The decision on the results of partial hypothesis testing can be concluded that there is an increase in Maharah Kalam learning outcomes after the Community Language Learning method experiment.